Influence of x-ray radiation on the antioxidant protection of the rat liver - Ya. G. Ivanushko; Yu. P. Grinevich; A. I. Lypska (Ядерна фізика та енергетика)
The impact of 30-day fractional x-ray irradiation in total doses of 0,3, 0,6, 0,9 and 1,2 Gy on antioxidant system of the rat liver has been studied. The superoxidedismutase, catalase, glutathione peroxidase activities of the liver homogenate decreased in all animal groups under study upon the termination of irradiation (the 1st 24-haur period) with a subsequent normalization by the 30th 24-hours period. The content of reduced glutathione changed in different directions (up to 10-days) upon the termination of radiation with a subsequent increase of its content in the rat liver by the 30th circadian period.